Novel prostate acid phosphatase‐based peptide vaccination strategy induces antigen‐specific T‐cell responses and limits tumour growth in mice. Issue 4 (7th March 2014) - Saif, Jaimy M. S.; Vadakekolathu, Jayakumar; Rane, Shraddha S.; McDonald, Danielle; Ahmad, Murrium; Mathieu, Morgan; Pockley, A. Graham; Durrant, Lindy; Metheringham, Rachael; Rees, Robert C.; McArdle, Stephanie E. B.
<x xml:space="preserve">Abstract</x> Treatment options for patients with advanced prostate cancer remain limited and rarely curative. Prostatic acid phosphatase (PAP) is a prostate‐specific protein overexpressed in 95% of prostate tumours. An FDA‐approved vaccine for the treatment of advanced prostate disease, PROVENGE® (sipuleucel‐T), has been shown to prolong survival, however the precise sequence of the PAP protein responsible for the outcome is unknown. As the PAP antigen is one of the very few prostate‐specific antigens for which there is a rodent equivalent with high homology, preclinical studies using PAP have the potential to be directly relevant to clinical setting. Here, we show three PAP epitopes naturally processed and presented in the context of HHDII/DR1 (114–128, 299–313, and 230–244). The PAP‐114‐128 epitope elicits CD4+ and CD8+ T‐cell‐specific responses in C57BL/6 mice. Furthermore, when immunised in a DNA vector format (ImmunoBody®), PAP‐114‐128 prevents and reduces the growth of transgenic adenocarcinoma of mouse prostate‐C1 prostate cancer cell‐derived tumours in both prophylactic and therapeutic settings. This anti‐tumour effect is associated with infiltration of CD8+ tumour‐infiltrating lymphocytes and the generation of high avidity T cells secreting elevated levels of IFN‐γ. PAP‐114‐128 therefore appears to be a highly relevant peptide on which to base vaccines for the treatment of prostate cancer.